2019
DOI: 10.11113/sh.v12n1.1419
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Web 2.0: GoAnimate.Com in Arabic Language Learning Activities at Universiti Malaysia Kelantan/ Penggunaan Aplikasi Web 2.0: GoAnimate.Com dalam Aktiviti Pembelajaran Bahasa Arab di Universiti Malaysia Kelantan

Abstract: This study is designed to present a web 2.0 application that provides multimedia and animated video known as GoAnimate.Com which has been used as a learning activity tool directly in Arabic teaching and learning (T&L) process. This activity was implemented in the class whereby the students were actively involved as practitioners and the teachers played the role as facilitators. The guidance to use GoAnimate.Com was explained to students by teachers before dividing them into groups. Each group were asked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Studies have found that heutagogy is only moderately practiced in Arabic lessons. This highlights the need to extend this practice, specifically in higher education institutions in Malaysia (Yahya et al, 2013;Hamzah et al, 2019;Rahman & Ahmad, 2020;Hai et al, 2020;Yahaya et al, 2021;Ghani et al, 2022;Fuad & Al-Yahya, 2022). The development needs of this media kit are also due to the issues of speech, communication, and willingness to communicate (WTC) faced by Arabic language students in Malaysian universities (Haron, 2011;Ibrahim, 2013;Mohamad, 2009;Arshad & Bakar, 2012;Noor et al, 2014;Daud & Pisal, 2014;Tohlong, 2015;Borham, 2018;Rahman & Ahmad, 2020).…”
Section: Problem Statementmentioning
confidence: 99%
“…Studies have found that heutagogy is only moderately practiced in Arabic lessons. This highlights the need to extend this practice, specifically in higher education institutions in Malaysia (Yahya et al, 2013;Hamzah et al, 2019;Rahman & Ahmad, 2020;Hai et al, 2020;Yahaya et al, 2021;Ghani et al, 2022;Fuad & Al-Yahya, 2022). The development needs of this media kit are also due to the issues of speech, communication, and willingness to communicate (WTC) faced by Arabic language students in Malaysian universities (Haron, 2011;Ibrahim, 2013;Mohamad, 2009;Arshad & Bakar, 2012;Noor et al, 2014;Daud & Pisal, 2014;Tohlong, 2015;Borham, 2018;Rahman & Ahmad, 2020).…”
Section: Problem Statementmentioning
confidence: 99%